A Novel Synthetic Dual Agonistic Liposomal TLR4/7 Adjuvant Promotes Broad Immune Responses in an Influenza Vaccine With Minimal Reactogenicity - Sato-Kaneko, Fumi; Yao, Shiyin; Lao, Fitzgerald S.; Shpigelman, Jonathan; Messer, Karen; Pu, Minya; Shukla, Nikunj M.; Cottam, Howard B.; Chan, Michael; Chu, Paul J.; Burkhart, David; Schoener, Roman; et al. (Frontiers in Immunology, 2020)
The limited efficacy of seasonal influenza vaccines is usually attributed to ongoing variation in the major antigenic targets for protective antibody responses including hemagglutinin (HA) and neuraminidase (NA). Hence, vaccine development has largely focused on broadening antigenic epitopes to generate cross-reactive protection. However, the vaccine adjuvant component which can accelerate, enhance and prolong antigenic immune responses, can also increase the breadth of these responses. We previously demonstrated that the combination of synthetic small-molecule Toll-like receptor 4 (TLR4) and TLR7 ligands is a potent adjuvant for recombinant influenza virus HA, inducing rapid and sustained antibody responses that are protective against influenza viruses in homologous and heterologous murine challenge models. To further enhance adjuvant efficacy, we performed a structure-activity relationship study for the TLR4 ligand, N-cyclohexy-2-((5-methyl-4-oxo-3-phenyl-4,5-dihydro-3H-pyrimido[5,4-b]indol-2-yl)thio)acetamide (C25H26N4O2S; 1Z105), and identified the 8-(furan-2-yl) substituted pyrimido[5,4-b]indole analog (C29H28N4O3S; 2B182C) as a derivative with higher potency in activating both human and mouse TLR4-NF-B reporter cells and primary cells. In a prime-boost immunization model using inactivated influenza A virus [IIAV; A/California/04/2009 (H1N1)pdm09], 2B182C used as adjuvant induced higher serum anti-HA and anti-NA IgG1 levels compared to 1Z105, and also increased the anti-NA IgG2a response. In combination with a TLR7 ligand, 1V270, 2B182C induced equivalent levels of anti-NA and anti-HA IgG1 to 1V270+1Z105. However, the combination of 1V270+2B182C induced 10-fold higher anti-HA and anti-NA IgG2a levels compared to 1V270+1Z105. A stable liposomal formulation of 1V270+2B182C was developed, which synergistically enhanced anti-HA and anti-NA IgG1 and IgG2a responses without demonstrable reactogenicity after intramuscular injection. Notably, vaccination with IIAV plus the liposomal formulation of 1V270+2B182C protected mice against lethal homologous influenza virus (H1N1)pdm09 challenge and reduced lung viral titers and cytokine levels. The combination adjuvant induced a greater diversity in B cell clonotypes of immunoglobulin heavy chain (IGH) genes in the draining lymph nodes and antibodies against a broad spectrum of HA epitopes encompassing HA head and stalk domains and with cross-reactivity against different subtypes of HA and NA. This novel combination liposomal adjuvant contributes to a more broadly protective vaccine while demonstrating an attractive safety profile.